2009
DOI: 10.2495/rm090261
|View full text |Cite
|
Sign up to set email alerts
|

Design of stream barbs for field scale application at Sawmill Creek, Ottawa

Abstract: A three-dimensional numerical model Simulation in Intakes with Multiblock option (SSIIM) was used to model the effects of placing a series of barbs along an unstable section of Sawmill Creek, a small urban stream in the city of Ottawa, Canada. Stream barbs (a type of submerged groyne) are low-profile linear rock structures that prevent the erosion of stream banks by redirecting high velocity flow away from the bank. As they can be built at a relatively low cost and also provide significant ecological benefit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, this outer bank erosion was not observed downstream of any of the other barbs. This singular occurrence of outer bank erosion was likely due to: (1) B2 being located in the most dynamic region of the two bends, as determined by the numerical modelling [5]; and (2) compared to the other barbs, the barb crest slope at T19 (B2) was the steepest (> 50 %) (Fig. 6), and therefore permitted the greatest amount of overtopping flow in this region.…”
Section: Channel and Barb Topographymentioning
confidence: 99%
See 3 more Smart Citations
“…However, this outer bank erosion was not observed downstream of any of the other barbs. This singular occurrence of outer bank erosion was likely due to: (1) B2 being located in the most dynamic region of the two bends, as determined by the numerical modelling [5]; and (2) compared to the other barbs, the barb crest slope at T19 (B2) was the steepest (> 50 %) (Fig. 6), and therefore permitted the greatest amount of overtopping flow in this region.…”
Section: Channel and Barb Topographymentioning
confidence: 99%
“…These surveys focus on the flow field in bend 1 only, where it was expected the barbs would have the greatest influence on the flow and morphology. This expectation was based on; (1) the more typical pool geometry in this bend versus the second bend, and (2) the results of the numerical modelling that established the optimum barb design for the site [5]. The numerical study found that the outer bank of the first bend (from T20 -T16, Fig.…”
Section: Study Site and Monitoring Programmentioning
confidence: 99%
See 2 more Smart Citations
“…The barb installation design for this project was reported by Jamieson [5]. Initial evaluation of the influence of barb installation on channel hydraulics and morphology was described in Jamieson [6,7].…”
Section: Introductionmentioning
confidence: 99%